Qualidade da cana-de-açúcar avaliadas nas partes do colmo - Silva Neto, Hélio Francisco da [UNESP] (2014)
The detailed study of the constituent parts from sugarcane stalks by means of biochemical and technological analysis, may enable a thorough knowledge of the quality of the juice and thus aid in several actions throughout the process of industrialization. Therefore, this study was conducted in order to compare different parts of the sugarcane cultivars stlaks, and their influence on the quality of the raw material. The collections of the sugarcane stalks occurred in Fazenda de Ensino Pesquisa e Extensão from FCAV/UNESP-Jaboticabal, SP. The biochemical and technological analyzes were performed at the Laboratório de Tecnologia do Açúcar e Etanol in the same University. The cultivars showed differences in the studied variables, and the cultivar SP81-3250 showed the most satisfactory results. The juice extracted from internodes had a higher percentage of apparent sucrose level, total reducing sugars, inorganic phosphorus levels and lower content of polysaccharides and enzymatic activity of polyphenol oxidase and peroxidase. In reverse, node juice had low quality, throughout the crop, showing their lower predisposition to produce sugar. The upper third of the stalk and the presence of the bark showed higher enzyme activity, which could provide cane juice darker, hindering the production of quality sugar. The region of the stalk represented by internode got greater potential for bioenergy generation